Gaya Komunikasi Perempuan Pengurus Organisasi - Munthe, Erlina; Ayub, Daeng; Syafitra, Viony (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2025)
Abstract: The existence of stereotypes in terms of management, how does female management influence the organization, so the purpose of this study is to determine and analyze the influence of women's communication style on the organization of the FKIP University of Riau student association. This study was located in the FKIP University of Riau student association organization. This research method is quantitative with data collection through observation, documentation, and questionnaires. The sampling method with simple random sampling using the Slovin formula, then the sample was 71 female organizational administrators from 4 study programs (community education science, elementary school teacher education science, guidance and counseling education science, and early childhood teacher education science). The results of the study are that women's communication style in organizations is influenced by demographic background, especially the class and study program. The class of 2023 showed the highest influence of communication style with a mean value of 4.34. Meanwhile, in terms of study programs, Community Education Science recorded the highest mean value of 4.38. Overall, each indicator of the results of this study confirms that women's communication style, especially the controlling style, has an important role in influencing the dynamics and effectiveness of student association organizations. Abstrak: Adanya stereotip dalam hal kepengurusan, bagaimana pengaruh kepengurusan perempuan terhadap organisasi, sehingga tujuan dari penelitian ini adalah untuk mengetahui dan menganalisis pengaruh gaya komunikasi perempuan terhadap organisasi himpunan mahasiswa Fkip Universitas Riau. Penelitian ini berlokasi di organisasi himpunan mahasiswa fkip Universitas Riau. Metode penelitian ini ialah kuantitatif dengan pengumpulan data melalui observasi, dokumentasi, dan angket. Metode sampling dengan simple random sampling dengan menggunakan rumus Slovin, maka sampel 71 perempuan pengurus organisasi dari 4 program studi ( ilmu pendidikan masyarakat, ilmu pendidikan guru sekolah dasar, ilmu pendidikan bimbingan konseling, dan ilmu pendidikan guru paud). Hasil penelitian adalah Gaya Komunikasi Perempuan dalam organisasi dipengaruhi oleh latar belakang demografis, terutama angkatan dan program studi. Angkatan 2023 menunjukkan pengaruh gaya komunikasi yang paling tinggi dengan nilai mean 4,34. Sementara itu, dari segi program studi, Ilmu Pendidikan Masyarakat mencatat nilai mean tertinggi sebesar 4,38, Secara keseluruhan dari masing-masing indikator hasil penelitian ini menegaskan bahwa gaya komunikasi perempuan, khususnya gaya mengendalikan, memiliki peranan penting dalam mempengaruhi dinamika dan efektivitas organisasi himpunan mahasiswa.